2022
DOI: 10.1186/s13045-022-01391-4
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies for EGFR-mutated non-small cell lung cancer patients with osimertinib resistance

Abstract: Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) are the preferential options for advanced non-small cell lung cancer (NSCLC) patients harboring EGFR mutations. Osimertinib is a potent irreversible third-generation EGFR-TKI targeting EGFR mutations but has little effect on wild-type EGFR. In view of its remarkable efficacy and manageable safety, osimertinib was recommended as the standard first-line treatment for advanced or metastatic NSCLC patients with EGFR mutations. However, as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 249 publications
(302 reference statements)
0
51
0
1
Order By: Relevance
“…The role of the EGFR gene is to control the cell's synthesis of the EGFR, which binds to the EGF in body fluids, thus initiating a series of biochemical reactions that promote the synthesis of DNA and mitosis. When a cell's EGFR gene is mutated, the EGFR produced by the cell continues to send a "division signal" to the cell, causing the cell to proliferate without control and evade apoptosis, which eventually result in a malignant tumor [5] . To treat this type of lung cancer, scientists have created three generations of drugs that specifically target different types of mutations and bind to EGFR on cancer cells, thereby controlling tumor growth, preventing tumor angiogenesis and inducing cancer cell death [17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the EGFR gene is to control the cell's synthesis of the EGFR, which binds to the EGF in body fluids, thus initiating a series of biochemical reactions that promote the synthesis of DNA and mitosis. When a cell's EGFR gene is mutated, the EGFR produced by the cell continues to send a "division signal" to the cell, causing the cell to proliferate without control and evade apoptosis, which eventually result in a malignant tumor [5] . To treat this type of lung cancer, scientists have created three generations of drugs that specifically target different types of mutations and bind to EGFR on cancer cells, thereby controlling tumor growth, preventing tumor angiogenesis and inducing cancer cell death [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous data told us that the median progression-free survival (mPFS) was 18.9 months in the Osimertinib treatment group, which is 8.7 months longer than that in the standard EGFR-TKI group [14] . However, just like any other EGFR-TKIs, Osimertinib inevitably develops acquired resistance, which limits its efficacy in treating patients with EGFR-mutated NSCLC [5] 。 The mechanisms of Osimertinib resistance identified so far can be roughly divided into two categories: targeted EGFR-dependent and off-target EGFR-independent mechanisms, including changes in the EGFR pathway, such as the C797S mutation; bypass activation, such as cellular Mesenchymal-Epithelial Transition (cMET) amplification, human epidermal growth factor receptor-2 (HER2) alteration, EGFR amplification, histological type changes, such as conversion to SCLC [15] . The combination of Osimertinib with bypass targeted therapy and other therapeutic approaches is a promising strategy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms of resistance to osimertinib are diverse, and some studies have suggested that the occurrence of T790M deletion after osimertinib resistance in most cases means that other off-target resistance mechanisms (such as MET amplification [7] and SCLC transformation [11]) are generated. Thus, repurusing of the first two generations of EGFR-TKIs is not always effective, and treatment is successful for a small fortunate subset of patients [19]. In addition, genetic testing showed activation of the ERK/MAPK signaling pathway, which may be one of the causes of resistance to EGFR-TKIs [20].…”
Section: Discussionmentioning
confidence: 99%
“…To test for EGFR-dependent osimertinib resistance in isolated OR populations, we sequenced the kinase domains of 25 OR populations, however, no mutations were found (data not shown). The most common EGFR-independent mechanisms involve reactivation of RTK/RAS signaling caused by either mutation or increased expression of parallel RKTs (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) including MET (24), FGFR (33,34), IGF1R (28,35), RET (36), and AXL (29)(30)(31), among others (7); and simultaneous activation of multiple RTKs often occurs within the same patient (5). We evaluated OR cell lines for changes in magnitude of receptor tyrosine phosphorylation compared to parental H1975 cells using phospho-tyrosine RTK arrays (Fig.…”
Section: Rtk Phosphorylation Is Heterogeneously Upregulated In Osimer...mentioning
confidence: 99%
“…Historically, combination therapies have been based on identifying two or more active single agents with distinct mechanisms of action ( 2 ), and most current combination therapies include an oncogene-targeted therapy and a second drug that targets an independent mechanism that, if left targeted, causes resistance to the first agent ( 3, 4 ). While many of these approaches succeed in increasing windows of progression free survival (PFS) in patients, resistance still emerges, often due to the strikingly heterogeneous mechanisms of acquired drug resistance both intratumorally ( 5, 6 ) and across patients ( 7, 8 ). Thus, novel approaches are needed to identify combination therapies that not only address a single mechanism of acquired resistance but simultaneously prevent most common mechanisms of resistance to a given targeted therapy.…”
Section: Introductionmentioning
confidence: 99%